Hippopotamus based optimization for reliable and cost-effective designing of stand-alone hybrid renewable system for a remote area - Gupta, Sanjeev; Sawle, Yashwant; Thakre, Kishor; Thirunavukkarasu, M. (Frontiers in Energy Research, 2025)
Energy is an important aspect of a country’s long-term growth, and to meet the increasing electrical demand for reliable manner, there is an urge to plan for future generations. In this study, metaheuristic optimization approaches that have recently been constructed, which include the coati optimization algorithm and hippopotamus optimization, were applied to determine the perfect dimensions for a grid-independent composite renewable energy infrastructure. The optimization problem attempts to reduce the total annual cost of the system while maintaining the reliability of the loss of power supply probability in an acceptable range. Three combinations of hybrid energy systems were designed and optimized, and the optimization findings point out that the system consisting of a photovoltaic module, wind turbine, storage battery, and battery is the most cost-effective optimal energy system. The lowest total annual cost of the PV/WT/SB/DG system obtained by using HOA is 24473, followed by PV/WT/DG at 26270 and PV/SB/DG at 35848. Also, the outcomes of the proposed algorithm were contrasted with those of the HOMER platform. When contrasting the effectiveness of optimization methods, the HOA is the optimal solution for resolving the sizing issue since it offers the most effective compromise among robustness, accuracy, and convergence rate.